Poverty Line Based on the Large Archipelagic Area in Indonesia in Taking Poverty Alleviation Policies - Royhan Faradis; Uswatun Nurul Afifah (JIET (Jurnal Ilmu Ekonomi Terapan), 2023)
Various efforts to overcome poverty have been carried out by the government but the number of poor people is still quite high. Based on the 1945 Constitution, the Indonesian government has a mandate to realize social welfare for all people. Well-being is characterized by the fulfillment of the material, spiritual, and social needs of citizens. In other words, prosperity can be achieved through poverty alleviation. In alleviating poverty, existing policies have not interpreted the poverty line based on division in Indonesia. This study analyzes more deeply the role of urban and rural poverty lines in the division of regions in Indonesia. The method used is descriptive statistics by grouping provinces into 7 categories of large islands in Indonesia. In addition, the MANOVA analysis method was also used in this study to answer the role of the region on the size of the poverty line. What is interesting about this study is the finding that regional differences play a significant role in influencing the size of the poverty line. This research also revealed the fact that the poverty line gap between regional categories is wide at a significance level below 0.05 in the MANOVA test of between subjects effects.